A Plain & Easy Introduction to the Harpsichord - Nurmi, Ruth (Albuquerque University of New Mexico Press, 1974)
Provides basic information on the harpsichord, best-known instrument of baroque music, including physical properties, kinds of harpsichords available, instruction on tuning and common maintenance problems, explanations of technique and fingering, tempo, registration, ensemble playing, and special notational problems.
Keywords: Harpsichord; Method; Musical interpretation; Ornamentation